Preferential purification of oxygenated volatile organic compounds than monoaromatics emitted from paint spray booth and risk attenuation by the integrated decontamination technique. (1st April 2017) - Chen, Jiangyao; Liu, Ranran; Gao, Yanpeng; Li, Guiying; An, Taicheng
Abstract: Purification and risk attenuation of mixed oxygenated volatile organic compounds (OVOCs) and monoaromatics (total concentration: 5.8 × 10 5 –1.2 × 10 6  μg m −3 ) from a paint spray booth of auto 4S shop were investigated. The applied integrated technique of spray tower (ST) with photocatalysis (PC) displayed 2.5 times higher elimination capacity (EC) to OVOCs (309.9 g m −3 h −1 ) than monoaromatics (124.5 g m −3 h −1 ), due to higher synergetic elimination of these two techniques. Specifically, approximately 4.3 times higher amount of OVOCs than monoaromatics was removed by ST, contributing to their two orders of magnitude higher Henry's law constants. Similar EC trend was also observed on PC (774.5 g m −3 h −1  > 518.5 g m −3 h −1 ). The corresponding quantum chemical calculation revealed more negative adsorption energy of OVOCs (−40.29 kcal mo1 −1 ) than monoaromatics (−33.32 kcal mo1 −1 ) onto the catalyst, resulting in more spontaneous and easy adsorption, enrichment and later degradation. Furthermore, the integrated technique displayed preferential and efficient reduction ability to both acute inhalation and chronic occupational exposure risks of OVOCs than monoaromatics. This study provided an efficient and pertinent approach to atmospheric purification and human health protection in motorvehicle repair business. Graphical abstract: Highlights: Elimination of VOCs during paint spray process. ST-PC integrated technique show high and stable removal ability to VOCs. ST and PC prefer the degradation of OVOCs than monoaromatics. Higher solubility to water and better adsorption affinity to the catalyst of OVOCs. Acute and chronic risks of VOCs decrease significantly after the treatment.